Thyroid Function in Chronically Transfused Children with Beta Thalassemia Major: A Cross-Sectional Hospital Based Study - Suraj Haridas Upadya; M. S. Rukmini; Sowmya Sundararajan; B. Shantharam Baliga; Nutan Kamath (Hindawi Limited, 2018)
Background. Thalassemia is the most common genetic disorder worldwide. Use of iron chelators has improved survival but endocrine complications have become more frequent. The frequency of hypothyroidism in Beta Thalassemia Major (BTM) children ranges from 6 to 30 %. Thyroid dysfunction mainly occurs by gland infiltration, chronic tissue hypoxia, free radical injury, and organ siderosis. Objectives. (a) To evaluate the thyroid function status in chronically transfused children with BTM, in the first and second decade of life and (b) to study the influence of factors like duration and amount of blood transfusions, serum ferritin level, and iron chelation therapy on thyroid function. Methodology. BTM children, 3 years old and above, on regular blood transfusions with serum ferritin > 1500 mcg/l were included in the study. Thyroid function and ferritin assessment was done using ELISA kits. Autoimmune thyroiditis was ruled out by antithyroid peroxidase and antithyroglobulin antibody testing. Results. A study population of 83 children consisted of 49 boys (59%) and 34 girls (41%). 4.8% of the children had evidence of subclinical hypothyroidism. Among them two belonged to the first decade and the other two to the second decade of life. Mean TSH, FT4, and ferritin values among children with thyroid dysfunction were 6.38 ± 0.83 mIU/ml, 1.08 ± 0.45 ng/dl, and 3983.0±1698.30 ng/ml, respectively. The severity of thyroid dysfunction was statistically significantly associated with higher serum TSH values in children in the second decade of life with a p value = 0.001. No other significant correlation was found between oral chelation, amount and duration of blood transfusion, or serum ferritin levels. Conclusion. Subclinical hypothyroidism was the thyroid dysfunction observed in our study. Regular blood transfusions with adequate chelation may decrease incidence of thyroid dysfunction.